2016
DOI: 10.4172/2155-9600.1000551
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acid, Flavonoids and Antioxidant Activity of Common Brown Beans (Phaseolus vulgaris L.) Before and After Cooking

Abstract: This study aimed to evaluate the impact of thermal processing and soaking on the profiles and contents of phenolic compounds in brown beans, as well as their antioxidant activity. We evaluated the antioxidant activity of extracts and the contents of phenolic acids and flavonoids by high-performance liquid chromatography (HPLC). With the exception of chlorogenic acid, the contents of all of the other phenolic acids were increased by cooking. Kaempferol was only detected in samples treated by soaking followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Higher concentrations of flavonoids were found in the extract of cooked bean. This was consistent with Huber et al, 22 who reported that cooking increases the concentrations of flavonoids fractions in P. vulgaris especially catechin, quercetin and quercetin-3-glucoside and kaempferol and kaempferol-3-rutinoside. Quercetin was said to be very useful in the deterrence and management of cancer, inhibition of free radical generation by hydrogen peroxide, blockage of histamine generation and involved in the reversal of cognitive insufficiency 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Higher concentrations of flavonoids were found in the extract of cooked bean. This was consistent with Huber et al, 22 who reported that cooking increases the concentrations of flavonoids fractions in P. vulgaris especially catechin, quercetin and quercetin-3-glucoside and kaempferol and kaempferol-3-rutinoside. Quercetin was said to be very useful in the deterrence and management of cancer, inhibition of free radical generation by hydrogen peroxide, blockage of histamine generation and involved in the reversal of cognitive insufficiency 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Results of phenotypic characterization for antioxidant activity showed a great level of diversity ranging from 2.15 to 60.48 with the mean TEAC of 20.03 µmol TE/g (Table S3). The observed range and average TEAC in the studied germplasm was much higher than reported by Huber et al [52], Weidner et al [34], and Bojilov et al [53]. Antioxidant activity during 2018 at both locations was recorded as higher compared to 2017.…”
Section: Discussioncontrasting
confidence: 53%
“…These differences in the antioxidant activity of common seeds grown in different years have been previously explained to be influenced by environmental variations, crop management practices, and genetic differences [55]. Frequency distribution reflected that a good number of landraces acquired TEAC contents similar to the results of earlier studies [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. The ANOVA was performed within and across the four environments to evaluate the genotypic effect and explore the GEI for antioxidant capacity.…”
Section: Discussionmentioning
confidence: 74%
“…Large amounts of chlorogenic acid have been recorded in raw bean extracts (Huber et al, 2016). Our observation also agrees with some of the main flavonoids and phenolic acids reported in common beans (Chávez‐Mendoza & Sánchez, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The data analysis was performed using OpenLab CDS, ChemStation Edition software (Agilent Technologies). The compounds were first detected using a single MS scan in the 100–1,500 m / z range based on previously reported m/z ions in common/cooked beans, according to the elution time described in the literature followed by a targeted search based on the peaks showing major signals in the UV–Vis chromatograms (Huber, Brigide, Bolis, & Canniatti‐Brazaca, 2016; Lin, Harnly, Pastor‐Corrales, & Luthria, 2008).…”
Section: Methodsmentioning
confidence: 99%